The shape of things to come: the Equifax breach, the GDPR and open-source security. Issue 11 (November 2017) - Hedley, Daniel; Jacobs, Matthew
Abstract : Although the General Data Protection Regulation (GDPR) is being hailed as a sort of revolution, what it really represents is the law catching up with reality. The GDPR isn't alone, of course – in the information security space it is accompanied by the Network and Information Security Directive (NISD). Both the GDPR and NISD go into effect in May 2018. Although the General Data Protection Regulation (GDPR) is being hailed as a sort of revolution, what it really represents is the law catching up with reality. You will need be able to explain how you've addressed data privacy protection and justify your decisions if a data breach occurs after the regulations go into effect. Daniel Hedley of Irwin Mitchell LLP and Matthew Jacobs of Black Duck Software describe the consequences of not getting to grips with the GDPR and the processes and policies you need to get into place now.